All Minds on Deck? Assessing Distributed Strategic Capacity in Public-Sector Organizations. (March 2023) - de Jong, Jorrit; Waardenburg, Maurits; Steenbergen, Bertine; Vachon, Nicholas
Networked governance requires public managers to think and act strategically across organizational boundaries. Taking the literature on the transition from government to governance and its implications for Human Resource Management (HRM) as a starting point, we argue that not only top management, but also lower-level employees are likely to be involved in this work. In order to invest effectively in the strategic and collaborative competencies required for networked governance at all levels of the organization, one needs to be able to assess strategic capacity. This article develops an assessment framework based on an in-depth case study conducted in a government department in the Netherlands over a 6-month period. We evaluate an initial framework to assess strategic capacity derived from existing literature and propose an augmented framework that acknowledges the tension between different accountability relationships and the need for continuous, structured, reflective interaction between managers, employees, and key stakeholders.